Assessment of fine particles released from paper printing and shredding processes - Shin, Nara, author; Tsai, Candace Su-Jung, advisor; Reynolds, Stephen, committee member; Tong, Tiezheng, committee member (Colorado State University. Libraries, 2019)
In this study, we investigated the airborne particles released during paper printing and paper shredding processes in an attempt to characterize and differentiate these particles. Particle characteristics were studied with real-time instruments (RTI) to measure concentrations and with samplers to collect particles for subsequent microscopy and cytotoxicity analysis. The particles released by paper shredding were evaluated for cytotoxicity by using in vitro human lung epithelial cell models. A substantial amount of particles were released during both the shredding and printing processes. We found that the printing process caused substantial release of particles with sizes of less than 300 nm in the form of metal granules and graphite. These released particles contained various elements including Al, Ca, Cu, Fe, Mg, N, K, P, S, and Si. The particles released by the paper shredding processes were primarily nanoparticles and had a peak size between 27.4 nm and 36.5 nm. These paper particles contained elements including Al, Br Ca, Cl, Cr, Cu, Fe, Mg, N, Na, Ni P, S, and Si, as determined by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) and single-particle inductively coupled plasma-mass spectroscopy (SP-ICP-MS) analysis. Although various metals were identified in the paper particles, these particles did not elicit cytotoxicity to simian virus-transformed bronchial epithelial cells (BEAS2B) and immortalized normal human bronchial epithelial cells (HBE1). However, future studies should investigate other cytotoxicity effects of these paper particles in various types of lung cells to identify the potential health effects of the particles.